2012
DOI: 10.1177/0194599812460505
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Induced Sleep Endoscopy vs Awake Müller’s Maneuver in the Diagnosis of Severe Upper Airway Obstruction

Abstract: Objective To compare fiber-optic nasal endoscopy with Müller's maneuver (FNMM) against drug-induced sleep endoscopy (DISE) in diagnosing the presence of severe level-specific upper airway collapse in patients with obstructive sleep apnea/hypopnea syndrome (OSAHS). Study Design Case series with chart review. Setting Tertiary care academic center. Subjects and Methods Medical records of all adult patients undergoing diagnostic DISE as part of their surgical evaluation were reviewed. Patients were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 29 publications
4
73
2
1
Order By: Relevance
“…Currently, there are many methods for diagnosing glossopharyngeal obstruction. In addition to a series of commonly used tests while the patient is awake [3,8,9], examinations about localizing the site of obstruction during natural or induced sleep are relatively reliable [4,5,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are many methods for diagnosing glossopharyngeal obstruction. In addition to a series of commonly used tests while the patient is awake [3,8,9], examinations about localizing the site of obstruction during natural or induced sleep are relatively reliable [4,5,10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a series of commonly applied examinations while awake [8,9], examinations performed during natural or induced sleep are relatively accurate [4,5,10]. Nasopharyngeal tube (NPT) insertion can guarantee the responsibility of excluding the obstruction of the nasal cavity, nasopharyngeal and oropharyngeal airways.…”
Section: Introductionmentioning
confidence: 99%
“…Collapse or obstruction of the nasal, nasopharyngeal, oropharyngeal and glossopharyngeal areas can all be the cause. It has been demonstrated that the oropharyngeal area is the most common site of obstruction in OSAHS [7,8]. As the basic surgery for treating OSAHS, UPPP has been widely applied.…”
Section: Discussionmentioning
confidence: 99%
“…FTP, CT scan and endoscopic examination were conducted with conventional methods [4,7,8]. NPT-PSG procedures were described shortly as follows [9][10][11].…”
Section: Polysomnography (Psg) Monitoring and Upper Respiratory Tractmentioning
confidence: 99%
“…Furthermore, they found tongue base surgery and oral device treatment to have the highest rate of change, whereas the indications for tonsil surgery were comparable between DISE and OPDA. Soares et al [38] retrospectively analyzed 53 patients with OSA and compared OPDA (endoscopy with and without Müller's maneuver) to DISE (with propofol titration of 50/75 mcg/kg/min, the target level of sedation was that of light sleep with arousal to tactile but not vocal stimulation) in diagnosing the presence of severe ([75 % collapse) levelspecific upper airway collapse. OPDA and DISE did not differ significantly regarding the presence of severe retropalatal collapse, but did significantly differ in the incidence of severe retrolingual collapse (DISE 84.9 %, OPDA 35.8 %).…”
Section: Dise: Sedation Methods Contraindications and Complicationsmentioning
confidence: 99%